THE COURSE OF BEHÇET’S DISEASE FOLLOWING COVID-19 DIAGNOSIS: A LARGE RETROSPECTIVE COHORT STUDY - Tuğba Atcı; Yasemin Erdem; Dilay Yerlioğlu Ak; Afet Akdağ Köse (İstanbul Tıp Fakültesi Dergisi)
Objective: Behçet’s disease (BD) is a chronic vasculitic disease with mucocutaneous and systemic involvements. This study aims to examine the effects of COVID-19 on the symptoms and course of BD. Material and Method: The BD patients who were followed up in our department with a history of COVID-19 were evaluated regarding the course of infection and the course of BD postCOVID diagnosis, assessed by Behçet’s Disease Activity Index (BDAI). Result: Among 449 BD patients, 68 (15.1%) had contracted COVID-19. The mean age of the patients was 42.7±11.8 years of whom 63.2% (n=43) were female. While most (n=48, 70.6%) had only mucocutaneous symptoms, others also had systemic symptoms (n=20, 29.4%) during their BD course; 86.8% (n=59) had received colchicine only at the time of infection. Prior to infection, 85.3% (n=58) had been in remission (BDAI score of 0), while 14.7% (n=10) already had active BD (BDAI score between 1-3). Post-COVID-19 diagnosis, activation or exacerbation of activation was seen in 39.7% (n=27) of BD patients, as characterized by increased BDAI scores (BDAI score between 1-4). No change was recorded in 60.3% (n=41) of the patients. Disease activation in the BD patients was mostly mucocutaneous (n=21, 30.9%). Comparison of the BD patients’ BDAI scores pre- and post-COVID-19 diagnosis revealed the scores to be significantly elevated (p<0.001; z=-4.691), demonstrating the possible effects of COVID-19 on BD severity.Conclusion: COVID-19 infection may lead to activation of BD symptoms, with new organs being involved in some patients, which should be confirmed by prospective large series.